The methodological development and significance of emālī literature in hadith studies - Muhammed Furkan Dogan, Furkan Dogan; Ahmed Ali, Ahmed El-Mogtaba Bannga (IIUM Press, 2025)
Emālī literature comprises works authored by hadith scholars (muhaddiths or mumlīs) who dictated hadiths to their students in structured sessions known as imlā majālis. Initially limited to the transmission of the isnād (chain of narration) and matn (text), these works gradually evolved into comprehensive compilations that incorporated hadith commentary (sharḥ), systematic authentication (taḥrīj), comparative analysis of different transmission paths (ṭarīqs), and scholarly discussions concerning hadith verification and criticism (taḥqīq and naqd). The Emālī tradition thus played a pivotal role in safeguarding the authenticity of hadiths and ensuring the integrity of their transmission. This study first examines the methodological foundations of Emālī works and analyzes the scholarly techniques employed within them. It then highlights the contributions of prominent hadith scholars who actively participated in dictation sessions and produced influential Emālī texts. Finally, the historical development and transformation of this tradition are discussed, demonstrating its central importance in the advancement of hadith methodology. In conclusion, Emālī literature constitutes a vital academic heritage within hadith studies, significantly enriching the systematic transmission and analytical examination of hadith texts